2017
DOI: 10.1016/j.jsat.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude, abstinence, and alcohol use disorders: Report of a preliminary finding

Abstract: Gratitude is a central component of addiction recovery for many, yet it has received scant attention in addiction research. In a sample of 67 individuals entering abstinence-based alcohol-use-disorder treatment, this study employed gratitude and abstinence variables from sequential assessments (baseline, 6 months, 12 months) to model theorized causal relationships: gratitude would increase pre-post treatment and gratitude after treatment would predict greater percent days abstinent 6 months later. Neither hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
1
15
0
2
Order By: Relevance
“…A similar unexpected finding was reported in a study of trait gratitude among individuals diagnosed with DSM IV alcohol dependence who had attended abstinence-based treatment ( Krentzman, 2017 ). Trait gratitude is the dispositional tendency to feel thankful for positive things in life; individuals with high trait gratitude feel thankful more frequently, more intensely, and via a greater number of prompts ( Wood, Froh, & Geraghty, 2010 ).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…A similar unexpected finding was reported in a study of trait gratitude among individuals diagnosed with DSM IV alcohol dependence who had attended abstinence-based treatment ( Krentzman, 2017 ). Trait gratitude is the dispositional tendency to feel thankful for positive things in life; individuals with high trait gratitude feel thankful more frequently, more intensely, and via a greater number of prompts ( Wood, Froh, & Geraghty, 2010 ).…”
Section: Introductionsupporting
confidence: 84%
“…The current study makes maximum use of the final follow-up assessment of trait gratitude in the LTS. In the LTS, trait gratitude was assessed at baseline and at the six-month follow-up for only the first 67 participants (for an analysis of gratitude among these participants, see Krentzman, 2017 ). Gratitude was then dropped from the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Leung and Tong (2017) compared cohorts of clients who had substance misuse issues, finding that those who showed higher traits of gratitude showed stronger coping strategies and lower drug use. In contrast Krentzman (2017) found that clients from an alcohol treatment centre who did not abstain following treatment had high gratitude levels which was thought assisted them in ignoring their harmful behaviours and situations. Studies have shown that gratitude may benefit patients by lowering stress, depression and anxiety (Petrocchi and Couyoumdjian 2016;Disabato et al 2017) and by reporting less suicidal ideation (Huffman et al 2014;White et al 2017).…”
Section: Benefits Of Using Gratitude For Clientsmentioning
confidence: 92%
“…Efeitos adversos também são relatados na literatura em relação a técnicas de promoção de gratidão em casos específicos. Embora intervenções para o desenvolvimento de gratidão estejam empiricamente associadas a benefícios para a saúde e bem-estar na população não clínica (ver Cunha, Pellanda, & Reppold, 2018), evidências mostram que, entre alcoolistas, exercícios de gratidão são contraindicados àqueles que têm a abstinência como meta (Krentzman, 2017).…”
Section: Aspectos Mercadológicos Da Pp: a Incorporação De Seu Discursunclassified